Analisis Vulnerabilitas Situs Web Universitas Pamulang Menggunakan Nessus - Nursalam, Asep Herman; Subekti, R.P. Fiki Wisnu; Safitri, Astried Nirmala; Prasmono, Yossy Veifbrian Fitri; Otafiyani, Adila Indriyani (Jurnal Ilmu Komputer, 2024)
The Pamulang University (UNPAM) website is an official website that is used for various purposes. Therefore, website security needs to be maintained so that it is not exploited by irresponsible parties. Vulnerability analysis is one way to find out the vulnerabilities that exist in a system. This research aims to conduct vulnerability analysis on the UNPAM website using Nessus. The research results show that the UNPAM website has a high level of vulnerability. This is indicated by the existence of high and medium levels of vulnerability. These vulnerabilities can be exploited by irresponsible parties to attack the UNPAM website. To mitigate these vulnerabilities, UNPAM website managers can take preventative steps by upgrading to a cipher suite with a key length of 128 bits or more, verifying the authenticity of the SSL certificate, enabling DNSSEC and implementing a DNSSEC-enabled resolver, using a DNS firewall, and disabling TLS 1.0 and enabling TLS 1.2 or higher version.